Determination of aflatoxins M1, M2, B1, B2, G1 and G2 in peanut by modified QuEChERS method and ultra-high performance liquid chromatography-tandem mass spectrometry - André Victor Sartori; Juliana Swensson de Mattos; Yuri Pereira Souza; Rosana Pereira dos Santos; Maria Heloísa Paulino de Moraes; Armi Wanderley da Nóbrega (Fundação Oswaldo Cruz (FIOCRUZ), 2015)
A suitable method for routine analysis of aflatoxins M1, M2, B1, B2, G1, G2 in peanut by ultra-high performance liquid chromatography-tandem mass spectrometry was developed and validated. The sample preparation was performed using a triple partitioning (water/acetonitrile/hexane) modified Quick Easy Cheap Effective Rugged and Safe (QuEChERS) method. For the first time, this method is reportedly used for aflatoxins analysis in peanut. Satisfactory recoveries ranged from 71 to 101%, with relative standard deviation lower than 15% were obtained for the target aflatoxins. The determination coefficients were ≥ 0.99 which showed good linearity. The LOD and LOQ varied from 0.03 to 0.26 ng g-1 and 0.1 to 0.88 ng g-1, respectively. The validated method was successfully applied to for the determination of aflatoxins in ten peanut samples. Total aflatoxin concentration exceeded the maximum level permitted by the Brazilian regulation in one sample of roasted peanut, while aflatoxins M1 and M2 were detected respectively in three and in one of the samples. The results strongly suggest that peanuts and peanut products should be continuously monitored for the aflatoxins investigated in this work.